-3x-(5x+1)=

Simple and best practice solution for -3x-(5x+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-(5x+1)= equation:


Simplifying
-3x + -1(5x + 1) = 0

Reorder the terms:
-3x + -1(1 + 5x) = 0
-3x + (1 * -1 + 5x * -1) = 0
-3x + (-1 + -5x) = 0

Reorder the terms:
-1 + -3x + -5x = 0

Combine like terms: -3x + -5x = -8x
-1 + -8x = 0

Solving
-1 + -8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -8x = 0 + 1

Combine like terms: -1 + 1 = 0
0 + -8x = 0 + 1
-8x = 0 + 1

Combine like terms: 0 + 1 = 1
-8x = 1

Divide each side by '-8'.
x = -0.125

Simplifying
x = -0.125

See similar equations:

| 3(x-4)+6=5(x+1)+1 | | 7b-5=8b-6 | | 6n-4=n+11 | | 4X^2+1=325 | | 2=1.1+3(m+3) | | 5a=a | | x^2-17x-30= | | 4-0.5k=4 | | 4z-2=20-w | | 7x+6=-57 | | 5(c+4/5)+6=50 | | -3(3y-5x)-y= | | 7a+1=1 | | 5+4(n+9)=3 | | -x+1=13 | | 6=8(s-3/4)-20 | | 3y+6=-3y | | 9*4y=10 | | a-99=176 | | d^2-6d-7= | | x(13-5x)=7 | | (4x+3)-(x-4)=5x+13 | | r-54=29 | | 3(1+9x)=6(2-4x) | | 2p^3-6p^2+15-5p= | | 155+s=249 | | -6-(x-4)=-12 | | 7a^2+35=7-40a | | 100=4+32t | | (n-8)*6=42 | | 3x^3+6x^2-4x-8= | | 5x+3=(x+7)+3x |

Equations solver categories